Introduction to the book reviews - Vol. 34 Iss. 2 - Keenan, Elizabeth King (Clinical Social Work Journal, 2006)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00350 tex.type: [object Object]
Keywords: dept.swk

Patterns of interaction: Conceptualizing the crossroads between social structures, interpersonal actions, and psychological well-being - Keenan, Elizabeth King (Smith College Studies in Social Work, 2007)
Patterns of interaction theory directs social workers' attention to the relations between structures (psychological and social), and actions: the crossroads of continuity and change. Because it describes sequences of action by key participants that generate specific options at various points in a sequence, it serves as both theory and method for understanding and intervening with human beings and social structures. The use of patterns of interaction as an overarching construct illuminates the reciprocal relationships between social structures, interpersonal actions, and psychological well-being. This paper outlines a preliminary conceptualization of patterns of interaction theory and the methodology that grows out of it. The social service programs of Temporary Assistance to Needy Families (TANF) and a community-based case management welfare-to-work program illustrate how an ethical lens applied to patterns of interaction can help social workers intervene within complex relations to facilitate client growth. Patterns of interaction theory is a potentially effective way of describing and analyzing the therapeutic effects of a range of different social service programs.
tex.unique-id: ISI:000245064200005
Keywords: dept.swk; ⚠️ Invalid DOI

Introduction to the book reviews - Vol. 34 Iss. 4 - Keenan, Elizabeth King (Clinical Social Work Journal, 2006)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000241716500012
Keywords: dept.swk

Introduction to the book reviews - Vol. 34 Iss. 3 - Keenan, Elizabeth King (Clinical Social Work Journal, 2006)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000238828500012
Keywords: dept.swk

Parallel processes in community- based research - Keenan, Elizabeth King (Reflections: Narratives of Professional Helping (Click on Current or Archives; Registration Optional), 2005)
Citation Key Alias: lens.org/149-209-837-126-977
Keywords: dept.swk; peer-reviewed; ⛔ No DOI found

Working models: A tool for synthesizing psychology, culture, and power in everyday experiences and internal representations - Keenan, Elizabeth King (Smith College Studies in Social Work, 2003)
As social beings, we experience ourselves through interactions with others in daily routines that participate in the cultural practices and power relations of broader social structures. Social workers, and social scientists in general, however, have had difficulty conceptualizing and synthesizing this way of being in the world. This paper attempts to respond to that gap by discussing how clinical social workers can use the concept of working models as a tool for listening and understanding in psychotherapy. Utilizing a case example, the paper will discuss three working models, the enactment of power relations, cultural practices, and psychological processes, which provide an integrative framework to inform clinical work.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/018-182-490-831-257 tex.type: [object Object]
Keywords: dept.swk

Book Review: object relations theory and self psychology in social work practice. eda g. goldstein. new york: the free press, 2001, 303 pp., 35.00 - Keenan, Elizabeth King (Clinical Social Work Journal, 2002)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/046-691-955-325-014 tex.type: [object Object]
Keywords: book.review; dept.swk

Theorizing the Emergence of Change in Daily Living: Developing a Contextual Framework for Social Work Practice. - Keenan, Elizabeth King (2008)
Keywords: dept.swk; faculty_collection; sabbatical_report

A new perspective: the common factors model as a foundation for social work practice education - Cameron, Mark; Keenan, Elizabeth King (Journal of Teaching in Social Work, 2009)
Foundation social work practice education is critical to the preparation of BSW practitioners for professional practice and the establishment of a theoretical and skill base upon which graduate students may build competencies in the advanced curriculum. Issues in the foundation practice curriculum may hinder this development. The common factors model holds promise as an organizing framework for foundation social work practice education. This model may help to resolve some key issues in social work and social work education, and may provide a useful, coherent, and empirical base for the foundation practice curriculum. © Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-482-221-756-184 tex.type: [object Object]
Keywords: Common factors; Direct practice; Foundation curriculum; Practice education; dept.swk; peer-reviewed

Do social workers integrate sociocultural issues in mental health session dialogue?: an exploratory study of cross-cultural practice - Keenan, Elizabeth King; Tsang, A. Ka Tat; Bogo, Marion; George, Usha (Social Work in Mental Health, 2004)
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00196 tex.type: [object Object]
Keywords: dept.swk

Cacophony, polyphony or fugue: Exploring sociocultural concepts with social work students - Keenan, Elizabeth King; Miehls, Dennis; Moffatt, Kenneth; Orwat, John; White, Joyce (Smith College Studies in Social Work, 2004)
This paper documents some dialogue among the authors that emerged as each taught Master of Social Work students a course in sociocultural concepts. The instructors taught this required course from a common syllabus and the discussion reflects the authors' experiences in the delivery of the course material. At the time these dialogues took place, the instructors had recently changed the course format. Rather than teaching sociocultural concepts in isolation (eg. a class on sexism, a class on ageism, etc.), the instructors crafted the course content around central themes. Postmodern theories underscore much of the course content, and are synthesized both in this course and across the curriculum with feminist, psychodynamic, and cross-cultural practice theories. The paper begins by summarizing key post-modern theories that frame the course. Then, the authors respond to formulated questions that address multiple forms of identity development, ambiguity, and competing student ideologies that are manifest in classroom dynamics. Finally, the authors discuss their respective pedagogical and theoretical views and discuss their classroom experiences.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-164-803-188-190 tex.type: [object Object]
Keywords: dept.swk